Burnout Syndrome Among Catholic Clergy: A Systematic Review - Picornell-Gallar, Damián; González-Fraile, Eduardo (Journal of Religion and Health, 2023)
Burnout syndrome implies exhaustion, loss of motivation, low performance, and absenteeism. Catholic clergy are not exempt. This systematic review compiles and analyzes evidence related to burnout in Catholic clergy and potential modulating variables. Following the PRISMA methodology, systematic searches in different scientific databases identified 17 studies, revealing that burnout is related to age, personality traits, and type of priesthood. No relation between burnout and social support, self-care, spiritual practice, or workload was detected. It is necessary to adapt conceptual models to the peculiarities of burnout among clergy, extending assessment strategies and introducing working and organizational perspectives in the analysis of modulating variables, and in the development of prevention and intervention programs.
Keywords: assessment; Burnout; Catholic priests; prevention; systematic review; JCR; Scopus